(untitled) (Heritage, 2023)
This paper provides an inventory and distribution of consonant and vocal sounds in certain settlements in the lower parts of the river Sitnica (Banjska and Gojbulja villages) near Vucitrn. The main intention of the interpreted material is to show the phonetic peculiarities of the speech of Donja Sitnica on a synchronic level and thus contribute to the knowledge of Serbian languages in the area of Kosovo. It can be seen that the Kosovo-Resava substratum has suffered sediments from other dialects from the neighboring Albanian language, which defines the investigated languages as peripheral. Therefore, the structures of the researched micro zones can be recognized as having multiple influences, which come from the progressive stokavian speech, the Prizren – South Morava dialect, Montenegrin speech and non Slavic linguistic circumstances. In the vowel system, the influences from the first three directions are more present, while in consonantism there are noticeable features from the structure of the Albanian language.